Winter Park HS Concert Choir [v.2] - Winter Park High School Concert Choir (Florida, Estados Unidos); Jacobs, Trey
Resumen: Conferencia Nacional organizada por American Choral Directors Association en donde se presenta Winter Park HS Concert Choir
Contiene: Jubilate Deo / Wolfgang Amadeus Mozart--Abendlied / Josef Rheinberger--Adijo, Kerida /Joshua Jacabson--A dog known as ego / Lars-Erik Larsson--Alister McAlpines Lament / arranged by Ralph Vaughan Williams--The drinking gourd / arranged by André Thomas